Use of newly available febuxostat in a case of chronic tophaceous gout contraindicated to allopurinol and probenecid - Abdullah, Hilmi; Mohamad Ismail, Asmahan; Rosman, Azmillah (Malaysian Medical Associations, 2012)
Urate lowering therapy in this country has mainly been achieved by the use of allopurinol and probenecid. A new xanthine oxidase inhibitor called febuxostat has been approved in 2009 for treatment of hyperuricaemia in gout. In this report, we describe the management of a patient with chronic tophaceous gout using febuxostat. The reduction in serum uric acid to target levels was rapid, and the tophi size had also reduced significantly while on therapy. There was no unwanted side effect observed during the therapy. Therefore, febuxostat would be a useful alternative drug in the treatment of hyperuricaemia in gout patients who have contraindications to allopurinol and probenecid